The Ecological Paradigm of State Ownership Concept in Indonesia - MHD Zakiul Fikri (Jurnal Ilmu Hukum, 2020)
After the fourth amendment adds 2 sections to article 33 of the 1945 Constitution,those are sections (4) and (5), so the changes cannot be considered without legalconsequences. The environmental norm had been invited to article 33 section (4) of the constitution of Indonesia as the highest law in Indonesia. Hence, this article aims to explain the ecological paradigm framework of state ownership conceptwhich regulated in article 33 sections (2) and (3) of the 1945 Constitution. There are at least two issues that will be answered in this article, those are: first, how the laws, jurisprudence and legal expert explain the concept of state ownership; and second, how the configuration of the ecological paradigm of state ownership concept and its legal implication to using of Indonesian natural resources.